Studies on mononuclear chelates derived from substituted Schiff bases ligands (Part 1): Synthesis and characterization of a new salicyliden-p-aminoacetophenoneoxime and its complexes with Co(II), Ni(II), Cu(II) and Zn(II) - Canpolat, E; Kaya, M (Polish Chemical Soc, 2005)
The new ligand salicyliden-p-aminoacetophenoneoxime (LH) was synthesized from p-aminoacetophenoneoxime and salicylaldehyde under reflux in absolute ethanol. Mononuclear complexes with a metal:ligand ratio of 1:2 have been prepared with Co2+ Ni2+, Cu2+ and Zn2+ salts. Their structures have been elucidated on the basis of IR, H-1 and C-13-NMR spectra, electronic spectra, elemental analyses, magnetic susceptibility measurements, molar conductivity and thermogravimetric analyses. According to the results, it is suggested that two ligands are coordinated to each metal atom by hydroxyl and the imino nitrogen to form high spin tetrahedral complexes with Co2+, Ni2+, Cu2+ and diagmagnetic complex with Zn2+.
Keywords: Schiff bases; imine compounds; oxime compounds; transition metal complexes